Pengaruh Kreativitas dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha pada Mahasiswa Semester VIII Prodi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2024/2025 - Putriani, Apryla Ayu Yega; Nurmaning, Bina Andri (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the effect of creativity and entrepreneurship education on entrepreneurial interest in VIII semester students of the Economics Education Study Program, Bhinneka PGRI University, Tulungagung, Academic Year 2024/2025. The method used is quantitative with a descriptive approach. Data were collected through questionnaires distributed to 89 students. The results of the analysis show that there is a significant effect of creativity on entrepreneurial interest, with a t-count value of 5.774 which is greater than the t table (1.988) and a significance value of 0.000 which is less than 0.05. In addition, entrepreneurship education also has a significant effect on entrepreneurial interest, with a t-count value of 3.641 which is also greater than the t table (1.988) and a significance value of 0.000. Simultaneously, these two variables provide a significant contribution to entrepreneurial interest, with a calculated F value of 102,805 which is much larger than the F table (3.952) and a significance value of 0.000. From the results of this study, it can be concluded that both creativity and entrepreneurship education have an important role in shaping entrepreneurial interest among students.